Radiofrequency ablation for ampullary neoplasia with intraductal extension after endoscopic papillectomy: Systematic review and meta-analysis - Landim, Davi Lucena; de Moura, Diogo Turiani Hourneaux; Hirsch, Bruno Salomao; de Oliveira, Guilherme Henrique Peixoto; Veras, Matheus de Oliveira; Nunes, Felipe Giacobo; Cavassola, Paulo Ricardo Pavanatto; Bernardo, Wanderley Marques; Mahmood, Sultan; de Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2024)
Background and study aims Noninvasive ampullary neoplasms may be removed by surgery or endoscopy. However, given the morbidity and mortality associated with surgery, endoscopic papillectomy (EP) is the preferred approach. Radiofrequency ablation (RFA) after EP has emerged as a promising alternative therapy to avoid surgery after incomplete EP. Our goal was to evaluate the efficacy and safety of RFA for residual or recurrent lesions with intraductal extension after endoscopic papillectomy.Patients and methods The inclusion criteria include clinical trials, cohort studies, and case series evaluating patients with residual or recurrent lesions with intraductal extension after EP treated with RFA. Case reports, duplicated data, and studies with follow-up periods < 10 months were excluded. The metanalysis evaluated adverse events, surgical conversion rate, clinical success and recurrence.Results Seven studies were selected, totaling 124 patients. RFA was associated with a clinical success rate of 75.7% (95% confidence interval [CI] 65.0-88.0%; I2 = 23.484) in a mean follow-up period < 10 months. However, the biliary stricture rate was 22.2% (95% CI 12.1-28.4%; I2 = 61.030), 14.3% of pancreatitis (95% CI 8.8-22.3%; I2 < 0.001), 7.0% of cholangitis (95% CI 3.3-14.5%; I2 < 0.001), 4.0% of bleeding (95% CI 1.7-9.3%; I2 < 0.001), and recurrence of 24.3% (95% CI 16.0-35.0%; I2 = 23.484).Conclusions RFA is feasible and appears to be effective for managing residual or recurrent lesions with intraductal extension after EP. However, long-term follow-up and high-quality studies are required to confirm our findings.
Keywords: RFA and ablative methods; Strictures; Endoscopy Upper GI Tract; Pancreatobiliary (ERCP/PTCD)